PENYULUHAN PERAN DAN URGENSI PENATAAN RUANG PADA PELAJAR SEKOLAH MENENGAH ATAS/KAUM MUDA DI KECAMATAN GROGOL PETAMBURAN, JAKARTA BARAT - Martina Cecilia Adriana; Anita Sitawati Wartaman; Endrawati Fatimah; Riana Ayu Kusumadewi; Bregas Djiwandono Aji (Universitas Trisakti, 2022)
The community service aims to increase the knowledge and awareness of youth and high school students regarding the role and urgency of spatial planning in creating a better living environment. The method used in this activity is in the form of counseling which targets high school students and young people in the community of RT 06/RW 08, Tomang Village, Grogol Petamburan District, West Jakarta. The counseling was carried out offline using a zoom which presented three main points, namely: (1) the definition of space, (2) the urgency of spatial planning, and (3) the role of spatial planning. In addition, an evaluation was also carried out through a google form to find out the increase in understanding gained from this activity. The result of this Community Service is that the community gains insight into the urgency and role of spatial planning. Implementing lecturers also representing the campus have succeeded in making this activity as a campus communication medium in disseminating knowledge, teaching, and research results directly to the community. This activity was successful which was indicated from the discussions that took place between the participants and the implementing lecturers, as well as the results of the evaluation of the distributed questionnaires. Hopefully, the participants will understand from an earlier age, become more active and enthusiastic in campaigning, setting an example, and even being directly involved in spatial planning.